Teaching Empire and War: Animating Marginalized Histories in the Classroom. (1st October 2021) - Maguire, Anna; Gupta, Diya
Abstract: How can we teach 'forgotten' histories of war and empire in the classroom, responding to urgent needs to 'decolonize' the curriculum and pedagogic practice? This article reflects on an exercise in pedagogical experimentation – a 'widening participation' project based upon a series of workshops – to demonstrate a more global and 'messy' understanding of the role of empire in the First and Second World Wars and their commemoration. We discuss the role of students and teachers as co-producers of knowledge, engaging with race and colonialism in the classroom, and the intervention of such work in the project of 'decolonizing' curricula.